Lexicography and Theory: Clearing the Ground. (14th September 2018) - Adamska-Sałaciak, Arleta
Abstract: The paper offers some reflections on the notion of theory in relation to lexicography. The immediate impetus for it has come from Tarp (2008) and the reactions which that book provoked. Prominent among Tarp's concerns was the scientific status of lexicography and the related topic of a/the theory of lexicography. Without arguing with Tarp's proposed solutions – which others (notably Piotrowski 2009 and 2013) have done convincingly enough – the issue is here addressed from a more prosaic angle. The question whether lexicography is a science cannnot be meaningfully asked, let alone answered, without acknowledging the terminological confusion that clouds the picture: the (English) terms crucial to the debate – science, lexicography, theory – each have more than one recognized meaning and the concepts behind them are far from universal. We therefore examine the relevant terminology closely, taking into account interlingual correspondences, intralingual polysemy, and instances of use found in corpora. The discussion is complemented by a brief look at what (meta) lexicography actually does, which should throw some light on whether it can be accorded the status of a science.